The Scan, Sahih, Selamat roadshow: educating the public on the dangers of unregistered medications and health supplements / Izzati Abdul Halim Zaki and Dr. Gurmeet Kaur Surindar Singh - Abdul Halim Zaki, Izzati; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Scan, Sahih, Selamat programme was successfully conducted on January 18, 2023 jointly organised by the Bahagian Perkhidmatan Farmasi, Jabatan Kesihatan Negeri Selangor (BPF) and Faculty of Pharmacy, Universiti Teknologi MARA (UiTM). The roadshow was attended by YBrs. En. Dazafarullah bin Daud, Deputy Director General of Health (Pharmacy) Selangor, YBhg. Professor Dato' Dr. Abu Bakar Abdul Majeed, Dean, Faculty of Pharmacy UiTM, representative from Techno Secure Print Sdn. Bhd and the Pharmaceutical Services Program, Ministry of Health. All medications and health supplements in Malaysia must be registered with the Drug Control Authority (DCA) before they can be marketed for the public, in order to ensure its safety, efficacy, and quality. Registered products will have the MAL registration number and hologram safety label attached to each packaging. Currently, the widely used hologram known as Farmatag™ is supplied by Techno Secure Print Sdn. Bhd. Additionally, the company has developed an application to increase public awareness on registration of products called FarmaChecker which can be downloaded from Google Play Store, Apple App Store or Huawei App Gallery.